THE INTERACTION BETWEE THE EFFECTIVENESS OF FINANCIAL INSTITUTIONS AND THE FLOW OF FOREIGN INVESTMENT: AN INTEGRATIVE ANALYSIS IN THE ALGERIAN ECONOMY 2000-2023 - Sofiane Charef Benatia; Kamel Belfodil (Acta Economica, 2025)
This study aims to analyse the relationship between the effectiveness of financial institutions and foreign investment flows in light of time-series data. The results showed that the financial institutions effectiveness index remained relatively stable during the studied period, while the foreign investment flow index experienced noticeable fluctuations. Using unit root and cointegration tests, it was found that the two time series, FIEI and DFI, are stationary at level (I(0)) and do not suffer from unit root problems. Furthermore, the results of the bounds test showed the existence of cointegration between the two indices at 1%, 5% and 10% significance levels. Through the standard model, it was found that the FIEI (-1) index has a positive and statistically significant impact on foreign investment flow, while the FDI index did not show a significant effect. The equilibrium correction rate (ECT) was found to be 41.79%, indicating a continuous correction of the gap between actual and balanced values.